RURAL HUMAN TOPONYMY IN THE MUNICIPALITY OF ASSIS BRASIL, STATE OF ACRE: AN ANALYSIS OF SEMANTIC-MOTIVATIONAL ASPECTS - Melo de Sousa, Alexandre; Souza de Oliveira Silva, Sandra Mara (Revista de Letras Norte@mentos, 2022)
This article analyzes the rural toponyms of Assis Brasil (AC- BRAZIL), focusing on their semantic-motivational aspects. The methodology used was by Dick (1990, 1992), and the initial studies of the State toponyms was carried out by Sousa (2007). We aim to present the description and the analysis of rural toponymy in the municipality of Assis Brasil, in the State of Acre (Brazil), regarding semantic-motivational aspects. Data were selected from spreadsheets of rural settlements. They were recorded in lexicographical-toponymic forms as adapted from Dick’s proposal (2004). Findings showed: the greatest influence of anthroponyms (23,59%) is related to people who were somehow notable in the social, historical, and cultural context; hagiotoponyms (12,4%) are related to saints from the Catholic discourse; and zootoponyms (10,12%) refer to the local fauna.